Melatonin Alleviates Chilling Injury Symptom Development in Mango Fruit by Maintaining Intracellular Energy and Cell Wall and Membrane Stability - Bhardwaj, Renu; Aghdam, Morteza Soleimani; Arnao, Marino Bañon; Brecht, Jeffrey K.; Fawole, Olaniyi Amos; Pareek, Sunil (Frontiers in Nutrition, 2022)
Efficacy of the signalling molecule melatonin for alleviating chilling injury (CI) in mango (Mangifera indica L.) fruit was studied to investigate the potential role of membrane integrity, energy charge, and ripening-related changes in the development of CI and its management by melatonin. ‘Langra’ and ‘Gulab Jamun’ cultivar mango fruit were immersed in 100 µM melatonin before storage for 28 d at 5 °C with weekly transfers to shelf life at 25 °C. CI symptom development was associated with compositional and enzymatic aspects of textural changes, cell membrane deterioration, and chemical energy status. Melatonin-treated ‘Langra’ fruit exhibited very low CI (5 vs. 21 %) while ‘Gulab Jamun’ fruit exhibited higher CI (36 vs. 38 %) during 28 d of storage at 5 ± 1 °C. Higher chilling tolerance in melatonin-treated ‘Langra’ was associated with lower softening, ascribed to lower cell wall degrading exo- and endo-polygalacturonase, pectinesterase, and endo-1,4-β-D-glucanase. In addition, lower membrane deteriorating phospholipase D and lipoxygenase activity in melatonin-treated ‘Langra’ corresponded to lower palmitic and stearic acids and higher oleic, linoleic, and linolenic acids accumulation, thus higher unsaturated/saturated fatty acids ratio. Additionally, there was higher intracellular energy supply with melatonin, represented by higher adenylate energy charge (AEC) arising from higher ATP and ADP and lower AMP accumulation, related to higher H+-ATPase, Ca2+-ATPase, succinate dehydrogenase, and cytochrome c oxidase activities. This study for the first time provides evidence suggesting that melatonin alleviation of CI is related to preservation of membrane integrity, thereby protecting the intracellular energy supply, as well as preserving cell wall integrity via impeding cell wall degrading enzyme activities.